Problems Analysis in High School Biology Textbooks Based on Cognitive Domain of Bloom Taxonomy - Sari, Amna Fika; Ulfa, Syarifah Widya (FKIP Universitas Lampung, 2022)
The purpose of this study is to understand the consistency of questions in class X biology textbooks based on the types of Lower order thinking skills (LOTS) and Higher order thinking skills (HOTS). This descriptive study analyzed questions in high school biology textbook with publishers Erlangga and Prawira Intan. The results showed that the distribution of the LOTS cognitive domain for Erlangga i.e remembering (C1) of 3.75%, understanding (C2) of 95.4%, applying (C3) of 0.75%. Meanwhile, the appearance of the HOTS cognitive domain for Erlangga i.e analyzing (C4) of 70%, evaluating (C5) of 20%, and creating (C6) of 10%. In other publisher Prawira Intan, the LOTS category for C1 of 65.7%, C2 of 31.8%, C3 of 2.41%. The most HOTS cognitive domain in the book publisher Prawira Intan are C4 which is 66.6%, C5 of 20% , and C6 of 13.3%.Keywords: problem analysis, Biology textbooks, cognitive domain, Bloom taxonomy.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp833-843